2022
DOI: 10.1002/hsr2.513
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV2 hospital surveillance and control system with contact tracing for patients and health care workers at a large reference hospital in Spain during the first wave: An observational descriptive study

Abstract: Background and Aims During the first peak of the COVID‐19 pandemic, the Preventive Medicine Department and the Occupational Health Department at Hospital Clinic de Barcelona (HCB), a large Spanish referral hospital, developed an innovative comprehensive SARS‐CoV2 Surveillance and Control System (CoSy‐19) in order to preserve patients' and health care workers' (HCWs) safety. We aim to describe the CoSy‐19 and to assess the impact in the number of contacts that new cases generated along this time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The different technologies, aims, populations and settings among the included studies are presented in Table 3 . In total, 7 of the 14 included studies investigated the use of proximity sensing technology [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ], 6 reported analyses following the development/deployment of technologically enhanced contact tracing systems [ 26 , 27 , 28 , 29 , 30 , 31 ], while only 1 described the use of telephone interviews [ 32 ]. All studies were conducted in hospital settings, including departments at risk of infectious diseases/isolation rooms [ 19 , 23 ], paediatrics [ 21 , 24 , 28 ], emergency departments [ 20 , 28 ] and one study included additional data from a nursing home facility [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The different technologies, aims, populations and settings among the included studies are presented in Table 3 . In total, 7 of the 14 included studies investigated the use of proximity sensing technology [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ], 6 reported analyses following the development/deployment of technologically enhanced contact tracing systems [ 26 , 27 , 28 , 29 , 30 , 31 ], while only 1 described the use of telephone interviews [ 32 ]. All studies were conducted in hospital settings, including departments at risk of infectious diseases/isolation rooms [ 19 , 23 ], paediatrics [ 21 , 24 , 28 ], emergency departments [ 20 , 28 ] and one study included additional data from a nursing home facility [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Authors report that the majority of users found the tool useful and would recommend its use, with a minority experiencing difficulties in using the platform (specifically logging in). Following the coronavirus outbreak disease in 2019 (COVID-19), three studies report on automated contact tracing approaches [ 28 , 29 , 30 ]. Hong et al investigated the use of clinical event data from electronic health records (EHRs) to identify healthcare worker exposure by coronavirus patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The value of surveillance systems during the COVID-19 pandemic cannot be overstated (9). Insights from these systems and other hospital-based studies have been useful in identifying those at increased risk for severe outcomes and informing both pharmaceutical and non-pharmaceutical interventions against the disease(6, 25, 26, 27, 28, 29). Our study found that patients admitted between May 2020 and December 2022 with SARI had a higher mortality rate, especially those with COVID-19, compared to their non-SARI counterparts.…”
Section: Discussionmentioning
confidence: 99%